Competency of Vocational Education Teachers in the Society Era 5.0 - Faya Izma Alayda; Putu Sudira; Farid Mutohhari (Jurnal Pendidikan dan Pengajaran, 2022)
Mastery of competence in the era of society 5.0 for teachers and students along with the development of science and technology in vocational education is still far from satisfactory. This study aims to analyze how far the readiness of teacher competencies is in the era of society 5.0. This study uses a survey research design with a total involvement of 340 respondents from vocational education teachers. The questionnaire method was used to measure all competencies in the era of society 5.0 with a 4-Likert scale questionnaire instrument. Data were analyzed descriptively based on the average and percentage of each competency, and also analyzed using the independent sample t-test and post hoc Dunnett test. The results of the study revealed that all competencies in the era of society 5.0 in teachers were high and did not differ significantly in the coverage of all characteristics of the respondents. Vocational education as a human resource development institution has an important role in transforming learning based on the society 5.0 era to respond to the challenges that exist in that era.